Trastornos gastrointestinales en pacientes post colecistectomia previa. revisión sistemática - Orbea Fernández, Andrés Francisco (2025)
An updated systematic review of the literature published in PubMed between January 2019 and December 2023 in adult post-cholecystectomy patients was conducted to improve patient prognosis. Objective: To synthesize the evidence regarding gastrointestinal disorders in adults undergoing cholecystectomy through a systematic review. Methods: A systematic review was conducted, which aided the application of inclusion criteria. Five studies were selected that addressed etiological, pathophysiological, and risk factors, including clinical, surgical, and microbiological aspects. The findings highlighted sphincter of Oddi dysfunction and gastric etiology as determinants of the early onset of SCA. Results: Alteration of the intestinal microbiota, with variations in Firmicutes, Bacteroidetes, and Proteobacteria, was determined to be associated with symptom severity and therapeutic response. Furthermore, preoperative factors—such as prior dyspepsia and the patient's physical and psychological status—were identified as predictors of persistent symptoms. Conclusions: The methodological heterogeneity of the studies limited the comparability of results and underscored the need to standardize diagnostic criteria. Consequently, a multidisciplinary and personalized approach combining conventional interventions and microbiota modulation was suggested, as well as future research focusing on pathophysiological mechanisms, precise diagnostic criteria, and therapeutic strategies aimed at optimizing the diagnosis, treatment, and quality of life of postcholecystectomy patients.